Design of Computer Data Structure in Large Retail Business Management Information System Based on RFID - Hao, Mengzhen (2023 2nd International Conference for Innovation in Technology (INOCON), 2023)
Taking the implementation of RFID based logistics information system in chain retail enterprises as the background, this paper puts forward a set of quantitative and operable income methods for distribution information management system of large chain enterprises. In the income evaluation, a Mamdani type two-dimensional fuzzy controller is designed to estimate the growth of sales income; For cost evaluation, based on the cost theory of cross organizational process innovation, a calculation method that comprehensively considers the development cost, conversion cost, capital cost and implementation cost is proposed. Taking a chain retail enterprise as a case, this paper puts forward management improvement measures based on RFID system, calculates the net present value and internal rate of return of this investment, and the results show that this investment is valuable.